Diet and serum lipids: changes over socio-economic transition period in Lithuanian rural population - Kriaucioniene Vilma; Klumbiene Jurate; Petkeviciene Janina; Ramazauskiene Vitalija; Sakytė Edita (BMC, 2011)
Abstract Background Since regaining of independence in 1990, Lithuania has been undergoing substantial political, economic, and social changes that affected the nutrition habits of population. Dietary changes might have impact on the trends of dietary related risk factors of chronic diseases. The aim of the study was to compare trends in diet and lipid profile of Lithuanian rural population aged 25-64 during two decades of transition period (1987-2007). Methods Four cross-sectional surveys were conducted within the framework of the Countrywide Integrated Noncommunicable Diseases Intervention Programme in five regions of Lithuania in 1987, 1993, 1999, and 2007. For each survey, a stratified independent random sample was drawn from the lists of the inhabitants aged 25-64 years registered at the primary health care centres. Altogether 3127 men and 3857 women participated in the surveys. 24-hour recall was used for evaluation of dietary habits. Serum lipids were determined using enzymatic methods. Predicted changes of serum cholesterol were calculated by Keys equation. Results The percentage of energy from saturated fatty acids has decreased from 18.0 to 15.1 among men and from 17.6 to 14.8 among women over the period of 20 years. The average share of polyunsaturated fatty acids in total energy intake increased from 5.3% to 7.1% among men and from 4.9% to 7.3% among women. The mean intake of cholesterol declined among women. Favourable trends in fatty acids composition were caused by increased use of vegetable oil for cooking and replacement of butter spread with margarine. Since 1987, the mean value of total cholesterol has decreased by 0.6 mmol/l. Total dietary effect accounts for a 0.26 mmol/l (43.3%) decline in serum cholesterol among men and 0.31 mmol/l (50.8%) decline among women. Conclusions Improvement in the quality of fat intake was observed in Lithuanian rural population over two decades of transition period. Positive changes in diet, mainly reduction in saturated fatty acids intake, contributed to decline in serum cholesterol level. Strengthening of favourable trends in nutrition habits in Lithuanian population should be one of the most important strategies of cardiovascular diseases prevention.